THE CONTRIBUTION OF VESTIBULAR INFORMATION TO ADAPTIVE LOCOMOTION IN YOUNG AND OLDER INDIVIDUALS - Lilian Gobbi, T. B. [UNESP]; Moraes, Renato; Tais Goncalves, C. [UNESP]; Marins Francisco, H. P. [UNESP]; Camila Ricciardi, O. [UNESP]; Fabio Barbieri, A. [UNESP]; Marcelo Pereira, P. [UNESP]; Miyasike-daSilva, Veronica [UNESP]; Black, C. I. (Nova Science Publishers, Inc, 2010)
Sensorimotor processing is necessary to perform motor actions according to environmental demands. The influence of visual, somatosensory and vestibular information, as well as their interaction, is largely studied in relation to postural control. Sensory integration is also crucial during adaptive locomotion and depends on both the task and the individual constraints. Several studies have been designed to observe the effects of the visual system on walking behavior, whereas the role of vestibular information, which is responsible for detecting linear and angular accelerations of the head in space, remains unclear. In this way, a series of three experiments was developed to investigate the contribution of the vestibular system on adaptive walking. In the first study, two different ways of disrupting vestibular system information in young adults were compared. Caloric and rotational stimulations were applied and subjects were asked to estimate the disturbance perceived. Rotational stimulation proved to disturb the vestibular system more intensively. In the second experiment, after rotational stimulation we asked young adults to walk and step over an obstacle. The results revealed that subjects' walking pattern changed in the presence of vestibular perturbation when compared to the condition of no stimulation. In the third experiment we used the same procedures and tasks of Experiment 2, but in older adults with no history of vestibular sickness. Older adults also showed spatial and temporal adjustments in their walking pattern. The results of these studies allowed us to conclude that vestibular information is not used to control limb elevation over an obstacle, but it is quite important in controlling locomotion direction. In addition, involvement in physical activity programs seems to minimize the effects of vestibular deficits.
Keywords: human; aging; vestibular system; locomotion; obstacles